The Role of Koperasi and UMKM in Improving Communities: A Case Study of Greater Malang - Hadi, Abdul; Ulfiandi, Ihsan Zikri (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the role of cooperatives and Micro, Small, and Medium Enterprises (MSMEs) in improving the welfare of the community in Greater Malang which includes Malang City, Malang Regency, and Batu City. The approach used is qualitative with a case study method through in-depth interviews, observations, and documentation studies. The results of the study show that cooperatives play an important role in providing access to capital, financial education, and strengthening the economic solidarity of members. Meanwhile, MSMEs are the main drivers of the local economy by creating jobs, increasing community income, and encouraging product innovation based on local potential such as culinary, handicrafts, and agro-tourism. Synergy between cooperatives and MSMEs is beginning to take shape, but it is still not optimal due to limited managerial literacy and low adoption of digitalization. Support from the government, universities, and the private sector is an important factor to strengthen the capacity of cooperatives and MSMEs in improving community welfare in a sustainable manner.